An assessment of the efficacy and safety of dydrogesterone in women with ovarian endometrioma: An open‐label multicenter clinical study. (4th June 2021) - Kitawaki, Jo; Koga, Kaori; Kanzo, Takumi; Momoeda, Mikio
Abstract: Purpose: To assess the efficacy and safety of dydrogesterone in Japanese women with ovarian endometrioma in a real‐world setting. Methods: The post‐marketing study involved 15 sites in Japan. Dydrogesterone 10 mg twice daily orally was administered for 21 days (day 5‐25 of each menstrual cycle) for 4 cycles. The primary outcome measure was the change in ovarian endometrioma volume from baseline. Secondary outcome measures included total dysmenorrhea score (0 = absent to 3 = severe), severity of dysmenorrhea pain [0‐10cm visual analog scale (VAS)], serum carbohydrate antigen 125 (CA‐125) levels, and safety. Results: The study group comprised women with an endometrioma aged 20 to 49 (47.4% cases aged ≥40 years). Endometrioma volume was reduced in 50% (26/52), unchanged in 25% (13/52), and increased in 25% (13/52) of women from baseline to the end of cycle 5; three‐quarters of patients thus had either reduced or unchanged ovarian endometrioma volume. Dydrogesterone significantly reduced total dysmenorrhea scores and severity of dysmenorrhea pain VAS during treatment compared with baseline. CA‐125 levels were not significantly changed during the study. The incidence of adverse events and adverse drug reactions in 59 subjects was 13.6% and 11.9%. Conclusions: Dydrogesterone prevented an increase in endometrioma size in many women, and it also significantly improved total dysmenorrhea scores and severity of dysmenorrhea pain, and was well tolerated. The ClinicalTrials.gov identifier of the study was NCT02921763.